J. VASSALLO - Seamless: Digital Collage and Dirty Realism in Contemporary Architecture - González de Canales, Francisco (ZARCH, 2017)
Jesús VassalloSeamless: Digital Collage and Dirty Realism in Contemporary ArchitectureArchitecture at Rice/Park Books, Houston y Zúrich, 2016, 208 páginas. Idioma: inglés.Tapa dura. 38 €. ISBN-10: 3038600199. ISBN-13: 978-3038600190